Evaluating academics’ knowledge sharing intentions in Malaysian public universities - Muhammad Ashraf, Fauzi; Christine Nya, Ling Tan; Ramayah, Thurasamy; Ojo, Adedapo Oluwaseyi (University Malaya, 2019)
Academics are the pillars of Institutions of Higher Learning (IHLs) where knowledge is created and shared. Willing academics will determine the quality of knowledge being shared between themselves and their students. In this research, a pilot study is conducted among academics in public IHLs, whereby the theory of planned behaviour (TPB) is adapted to study the academics’ intention to share. Responses are obtained from 45 academics out of 399 survey questionnaires sent via email. This study uses the partial least square (PLS) method where variance-based structural equation modelling (SEM) is applied. The analysed data showed that social network, attitude, management support, social media, and perceived behavioural control (PBC) are significant factors for academics’ intention to share while commitment, trust and subjective norms are not significant. Perceived cost and facilitating conditions are significant but have a negative relationship with their knowledge sharing intention. Several limitations were observed, such as the use of cross-sectional study and the lack of moderating factors. This study would facilitate IHLs in identifying the relevant conditions to be addressed when appointing academics in warranting that academics would be sharing their knowledge for the benefits of the whole community, within and outside the IHLs.